2015
DOI: 10.28925/2414-0325.2015.1.20741
|View full text |Cite
|
Sign up to set email alerts
|

Open Educational E-Environment as Factor of Expanding Educational Offer and Increasing Quality of Education

Abstract: IntroductionThe rapid development of telecommunications and information technology, and the changes in the education system being brought about by this development are forcing universities, schools and other educational institutions not only to continuously improve their skills and tools but also to further improve their educational offering. The best way to enhance the image of universities and individual departments is to adequately build their own information space, which, thanks to technological advances c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…To check the pedagogical conditions for improving students' English language proficiency and stimulating them for lifelong learning, we used pedagogical technologies for intensifying students' activities based on applying ICT in the ESP classroom. Moodle platform was actively used during experimental teaching (see also Dougiamas & Taylor 2003;Rice, 2006;Smyrnova-Trybulska et al, 2015). However, the analysis of previous research on the problem has shown that still there is a research gap in organising ESP classroom activities as well as self-study work of future civil engineers by means of ICT.…”
Section: Resultsmentioning
confidence: 99%
“…To check the pedagogical conditions for improving students' English language proficiency and stimulating them for lifelong learning, we used pedagogical technologies for intensifying students' activities based on applying ICT in the ESP classroom. Moodle platform was actively used during experimental teaching (see also Dougiamas & Taylor 2003;Rice, 2006;Smyrnova-Trybulska et al, 2015). However, the analysis of previous research on the problem has shown that still there is a research gap in organising ESP classroom activities as well as self-study work of future civil engineers by means of ICT.…”
Section: Resultsmentioning
confidence: 99%
“…This may be related to an initial fascination with AI issues in the first year of study and the greatest knowledge about the possibilities of AI in the fifth year of study. Their interest in the topic is the motivation for the development of a platform and courses in the research area for students to deepen their knowledge and use it in their education and future professional career, which is what the FITPED-AI project serves (Skalka, & Drlik, 2022;Smyrnova-Trybulska, Drlik, & Skalka, 2023).…”
Section: Discussionmentioning
confidence: 99%